Work conditions and personal protective equipment against COVID-19 in health personnel, Lima-Peru: Condiciones laborales y equipos de protección personal contra el COVID-19 en personal de salud, Lima-Perú - Raraz Vidal, Jarvis Giusseppe (2021)
Objective: To determine the association between working conditions and access to personal protective equipment (PPE) in health personnel in the city of Lima-Perú. Methods: Descriptive, cross-sectional and analytical study. The sample was of 323 respondents virtually in the city of Lima, who met the selection criteria, captured between 07/09/2020 to 08/09/2020. The data collection instrument was validated by expert judgment with a score> 80% (content validity). An analysis was carried out with the generalized linear model of the poisson family, log link function, robust models with fit. A statistically significant value of p <0.05 was considered. Results: 52% of health personnels (HP) worked more than 12 hours and only 55% received one PPE per work day. 50.9% of the HCP almost never received a mask. In the multivariate analysis, the SP with ages <26 years (p=0.00) and from 26 to 55 years (p=0.00) received an incomplete PPE. HP who did not have an employment relationship with the institution (p=0.006) and those who worked in areas with little contact with COVID-19 patients (p=0.022) received a mask on few occasions. Conclusion: Health personnels under 56 years of age rarely received PPE. When they work without an employment relationship and belonged to areas with little contact with COVID-19 patients, they sometimes received a mask.